Directive Speech Acts of Harry Potter, Ronald Weasley, and Hermione Granger in “Harry Potter and The Philosophers Stone” Movie Script - Sartika, Dewi; Irawan, Andi Muhammad (English Language and Literature, 2021)
This study aims 1) to find out the directive speech acts used by Harry Potter, Ronald Weasley, and Hermione Granger in “Harry Potter and The Philosopher’s Stone” movie script; 2) to compare the use of directive speech acts between the three characters; and 3) to find out if context of situation influences the use of directive speech act between the three characters. This study is a descriptive qualitative and quantitative research, using the theory of Searle about directive speech act. The data of this study are utterances of Harry Potter, Ronald Weasley, and Hermione Granger which contain directive speech act found in “Harry Potter and The Philosopher’s Stone” movie script. The result of this study 1) shows that there are five types of directive speech act used by Harry Potter, Ronald Weasley, and Hermione Granger in “Harry Potter and The Philosopher’s Stone” movie script, they are command, request, permission, prohibition, and question; 2) reveals that different characters do not really influence the use of directive speech acts, which means that the use of directive speech acts between the three characters is similar in general 3) proves that context gives a great influence on the use of directive speech act.